Palladium-Catalyzed Desulfurative Hiyama Coupling of Thioureas to Achieve Amides via Selective C–N Bond Cleavage - He, Zhanyu; Yan, Chu; Zhang, Mei; Irfan, Majeed; Wang, Zijia; Zeng, Zhuo (Synthesis, 2021)
Palladium-catalyzed Hiyama coupling of active thioureas via selective C–N bond cleavage is reported. Notably, the new approach employed active thioureas as coupling partners in the presence of arylsilanes to give amides in good yield. Further, this strategy, which utilized CuF2 as a key oxidant and activator, afforded various amide products under mild conditions and an easy to handle procedure without extra base.
Keywords: desulfurative Hiyama coupling; CuF2 activator; thiourea; selective C–N bond cleavage; amide